GENERAL MOTOR FITNESS AND SOMATIC PARAMETERS COMPARISON BETWEEN FORMER POPULATION AND PRESENT PRIMARY SCHOOL GIRLS IN RUZOMBEROK - Peter KRSKA; Jaromir SEDLACEK; Andrej HUBINAK; Maria TEPLICANCOVA; Jan KOSTIAL (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Since 2014 we have started regular annual testing of somatic and general motor performance parameters in several maternal, primary and secondary schools (ISCED 0, 1 and 2) in northern small Slovak town Ruzomberok. This action has been supported also by municipality as well as by Faculty of Education, Departement of Physical Education and Sports. The project is called BUBO and is focussed on regular annually monitoring of measured parameters with the intention to prepare longitudinal materials for physical fitness improvement of young generation with the possibility also to find potentional talented children for sport practice. This contribution deals with girls from primary schools (age 6 - 11). We used two somatic tests body height (BH) and body weight (BW) and reduced Eurofit test battery for general motor performance level evaluation: sit and reach (SR), standing broad jump (SBJ), sit-ups in 30 s (SU), bent arm hang (BAH), shuttle run 10 x 5 m (10x5), endurance shuttle run (ENDU) plus 2 kg medicine ball throw (MBT) from former Czechoslovak test batteries. These parameters we compared with Slovak population results mostly from period of measurements 1994-95 and 1987 in case of MBT. Differences were evaluated by parametric un-pair test on 1% and 5% significance level. There were involved 411 girls from Ruzomberok 1st to 5th classes. In somatic parameters can be seen that former generation of girls are significantly taller than present girls; the older they are the greatest difference is seen. As the BW differences are mostly without statistical significance. That means that BMI of present generation reaches higher values. Results of motor performance level show that in test BAH are mostly significantly better girls from Ruzomberok, in test SR are results nearly equal, but in other tests are clearly better girls from former measurements, mostly on 1% significance level difference. The greatest differences can be seen in SBJ and in ENDU. It is seen that less favourable somatic parameters of present primary girls probably also negatively influence general motor performance level, which can be characterized like clear decrease comparing former measurements.